New Technology and the Non-Manual Labour Process in Britain - Smith, Anthony (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
Drawing on evidence from five detalled case studies, this paper focuses on the relationship between technical innovation and non-manual skills and work organization. In none of these cases could the introduction of new technologies simply equate technical innovation with deskilling and enhanced managerial control. Indeed, one of the more interesting and important findings of the research was that technological change has been more favourable for technical than for clerical occupational groups.